COMPLICATED PLASMODIUM FALCIPARUM MALARIA INITIALLY PRESENTING AS MYOCARDITIS - Khattak, Abdul Latif; Ali, Waqar; Samore, Naseer Ahmad; Idris, Muhammad; Khan, Muhammad Nadir; Pasha, Waseem (Journal of Ayub Medical College Abbottabad, 2014)
Despite recent advancements in diagnostic and treatment modalities, malaria is still one of the most prevalent human diseases with high mortality and morbidity. We described a case of 45 years old man with Plasmodium falciparum malaria primarily presenting with myocarditis. The possibility of malaria was subsequently considered when he developed fever followed by signs of cerebral involvement. This happens to be a distinctly unusual presentation and we highlighted various features of this case. Thus in hyperendemic areas complicated Plasomdium falciparum malaria may present initially with atypical features and high index of suspicion may lead to prompt early aggressive antimalarial therapy and reduce the complications. Keywords: Plasomdium falciparum, myocarditis, complications malaria